An inventory of lysosomal ABC transporters. Issue 23 (28th November 2020) - Szakacs, Gergely; Abele, Rupert
Abstract : ABC transporters fulfill diverse physiological functions in different cellular localizations ranging from the plasma membrane to intracellular membranous compartments. Several ABC transporters have been spotted in the endolysosomal system, which consists of endosomes, autophagosomes, lysosomes, and lysosome‐related organelles. In this review, we present an overview of lysosomal ABC transporters including ABCA2, ABCA3, ABCA5, ABCB6, ABCB9, and ABCD4, discussing their trafficking routes, putative substrates, potential physiological functions, and associated diseases. In addition, we offer a critical evaluation of the literature linking ABC transporters to lysosomal drug sequestration, examining pitfalls associated with in vitro models of drug resistance. Abstract :